The importance of P-glycoprotein multidrug transporter activity measurement in patients with Helicobacter pylori infection - Babić, Žarko, liječnik (Array, 2009)
Abstract: P-glycoprotein is important in local antibiotic resistance. Aim was to evaluate the role of P-glycoprotein in local antibiotic resistance in patients with antral gastritis during antibiotic therapy to Helicobacter pylori infection. In the group of 53 patients with pathohistologically verified gastritis and microbiologically confirmed H. pylori infection (no signs of antimicrobial resistance) we have determined P-glycoprotein activity in gastric mucosa biopsy specimens, and compared them with the P-glycoprotein activity in 12 control subjects with normal endoscopic findings. The H. pylori positive patients were treated according to Maastricht protocol with short-term 7-day therapy consisting of two antibiotics (amoxicillin and azithromycin/metronidazole and clarithromycin) and a proton pump inhibitor. P-glycoprotein activity was determined in rhodamine dye efflux test and quantified by ratio of the mean fluorescence (RMF) in flow cytometry analysis. H. pylori was successfully eradicated in the first cycle in 20 patients, whereas therapy was continued in 33 patients. The mean pre-treatment RMF values were higher in patients with H. pylori infection then in control subjects (p<0.0046). RMF was also higher in patients with multiple therapeutic failure than in those with successful H. pylori eradication (p<0.0001). RMF increased significantly during the antibiotic therapy (p<0.05). P-glycoprotein might be one of the causes of therapy failure in patients with H. pylori. Our study confirms the importance of quantitative evaluation of P-glycoprotein expression during antibiotic treatment response